Innovative technologies in corporate sales management: a review of the current state and future directions - V. V. Grigorian (Путеводитель предпринимателя)
The study analyzes the current state and prospects for the development of innovative technologies in corporate sales management. The theoretical foundations of sales management and the impact of technologies such as artificial intelligence, big data analytics, blockchain and IoT are examined. Results support the shift to predictive, data–driven approaches in sales due to the convergence of these technologies. Key implementation challenges are identified, including data security issues and the need for organizational adaptation. Successful integration of these technologies can provide a competitive advantage by improving customer understanding, optimizing processes, and creating new interaction models.